Stable Isotope Analysis of Mammalian Enamel From the Early Pleistocene Site of Madigou, Nihewan Basin: Implications for Reconstructing Hominin Paleoenvironmental Adaptations in North China - Xu, Zhe; Pei, Shuwen; Hu, Yaowu; de la Torre, Ignacio; Ma, Dongdong (Frontiers in Earth Science, 2021)
The reconstruction of environmental and climatic changes in the Pleistocene is an essential contribution to our understanding of human evolutionary and behavioral adaptations. Well preserved fluvio-lacustrine sediments at Nihewan basin have yielded a rich record of Early Pleistocene Paleolithic sites and mammalian fossils which provide a unique opportunity for exploring hominin behavior and paleoecology in North China. Taxonomic studies of mammalian fossils have provided important clues to the general environmental setting and landscapes of Early Pleistocene humans in the fluvio-lacustrine basin of Nihewan, but little is known about their isotopic signatures. In this paper, mammal teeth species at the Madigou archaeological site (ca. 1.2 Ma) were selected for bulk and sequential enamel stable isotope (C, O) analysis. Results show a variety of ecological environments, including grassland and sparse forest landscapes, and distinct patterns across taxa. C3-C4 mixed vegetation predominated, but C4 vegetation was also relevant at times. Madigou early humans likely experienced cold/warm or dry/wet fluctuations in this northern China basin. We hypothesize that the environmental fluctuations and diversified landscapes may have driven flexibility in various aspects of early human technological behaviors, and allowed hominins to face the environmental challenges of northern latitudes after the initial expansion from Africa into East Asia at the onset of the Middle Pleistocene Climate Transition.